Systematic unravelling of the biosynthesis of poly (L-diaminopropionic acid) in Streptomyces albulus PD-1 - Xu, Zhaoxian (Nature Publishing Group, 2015)
Poly(L-diaminopropionic acid) (PDAP) is one of the four homopoly(amino acid)s that have been discovered in nature. However, the molecular mechanism of PDAP biosynthesis has yet to be described. In this work, the general layout of the PDAP biosynthetic pathway is characterised in Streptomyces albulus PD-1 by genome mining, gene disruption, heterologous expression and in vitro feeding experiments. As a result, L-diaminopropionic acid (L-DAP), which is the monomer of PDAP, is shown to be jointly synthesised by two protein homologues of cysteine synthetase and ornithine cyclodeaminase. Then, L-DAP is assembled into PDAP by a novel nonribosomal peptide synthetase (NRPS) with classical adenylation and peptidyl carrier protein domains. However, instead of the traditional condensation or thioesterase domain of NRPSs, this NRPS has seven transmembrane domains surrounding three tandem soluble domains at the C-terminus. As far as we know, this novel single-module NRPS structure has only been reported in poly(ε-L-lysine) synthetase. The similar NRPS structure of PDAP synthetase and poly(ε-L-lysine) synthetase may be a common characteristic of homopoly(amino acid)s synthetases. In this case, we may discover and/or design more homopoly(amino acid)s by mining this kind of novel NRPS structure in the future.